Effects of selenization process on densification and microstructure of Cu(In, Ga)Se2 thin film prepared by doctor blading of CIGS nanoparticles. Issue 16 (November 2018) - Sun, Man-Ting; Yang, Chang-Ting; Wu, Yu-Chien; Hsiang, Hsing-I.
Abstract: Flaws, such as porous structure and small grains easily occur during Cu(In, Ga)Se2 (CIGS) thin film absorber preparation from nanocrystallites have been the major obstacle to practical application of this technology. The selenization process parameter effects on the densification, microstructure, and electrical properties were investigated in this study using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and Hall-effect analyzer. Grain size was observed nearly independent of the selenization time but increased with increasing selenium mass in the graphite box for selenized CIGS film at 500 °C. Pre-sintering at 2 bar N2 atmosphere overpressure can effectively suppress the in-plane tensile stress generated by the shrinkage mismatch between the CIGS and Mo-coated glass substrate during 500 °C sintering, leading to better densification. The pre-sintered and selenized CIGS film exhibited good electrical properties suitable for solar cell applications.